Chaos and Fear. The Essence of Wars in History according to Historical Sociology - Dominiak, Łukasz M. (Sensus Historiae, 2025)
Michael Mann’s latest book, On Wars (2023), is a monumental work of historical sociology, which, in addition to empirical material, presents an integral theory of war. The book analyzes wars throughout history, from ancient Rome and China, through Europe (1000–1945), to contemporary Japan, South America, and Muslim countries in the 20th and 21st centuries, concluding with remarks on the war in Ukraine. It covers both the macrosocial and microsociological perspectives (the fear and revulsion of soldiers and civilians). Mann sees war as a constant existential threat and an irrational and ineffective means of exercising power that has accompanied humanity for 5,000 years. He also notes that wars are not disappearing, but are becoming less predictable and fraught with the risk of unexpected consequences.